The Evaluation of Sustainable Profesional Development Program Through Madrasah Education Quality Reform Project to Enhance Students’ Learning Outcomes in Madrasah Tsanawiyah Banten Province - Wulandari, Astry; Gailea, Nurhaeda; Hidayat, Sholeh (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to improve students’ learning outcome through madrasah education quality reform project for English teacher professional. There was a problem in student learning outcome in Madrasah Tsanawiyah, the average of the national examination was under 50%. This study used evaluation model of countenance that was developed by Stake. There were three aspects in this evaluation, (1) context evaluation, (2) process evaluation and (3) outcome evaluation. The result of context evaluation showed that 57.5% the policy of program was appropriate with the activity and it was relevance with the trainee duties in workplace. Meanwhile the process evaluation showed 64,6% this program run well according to established plan. There was an increase students’ learning outcome in Madrasah assessment about 0,43%.